On the role of Rossby wave breaking in the quasi-biennial modulation of the stratospheric polar vortex during boreal winter - Lu, H; Hitchman, MH; Gray, LJ; Anstey, JA; Osprey, SM (Wiley, 2020)
The boreal‐winter stratospheric polar vortex is more disturbed when the quasi‐biennial oscillation (QBO) in the lower stratosphere is in its easterly phase (eQBO), and more stable during the westerly phase (wQBO). This so‐called “Holton‐Tan effect” (HTE) is known to involve Rossby waves (RWs) but the details remain obscure.